2022
DOI: 10.3390/nano12111822
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characterization and Cellular Toxicity Studies of Commercial NiO Nanoparticles

Abstract: Nickel oxide (NiO) nanoparticles from several manufacturers with different reported sizes and surface coatings were characterized prior to assessing their cellular toxicity. The physical characterization of these particles revealed that sizes often varied from those reported by the supplier, and that particles were heavily agglomerated when dispersed in water, resulting in a smaller surface area and larger hydrodynamic diameter upon dispersion. Cytotoxicity testing of these materials showed differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
2
3
1
Order By: Relevance
“…The Z-average and PDI measured in the cell culture medium were very similar to the data obtained in water and the measured values were reasonably stable over a period of 72 h, which is the maximum time required for the biological assays. These results are in contrast to those obtained in our earlier work on other metal oxide NPs for which the hydrodynamic diameter and polydispersity typically increased in cell culture medium compared to water and continued to increase with storage time [ 22 , 23 ].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The Z-average and PDI measured in the cell culture medium were very similar to the data obtained in water and the measured values were reasonably stable over a period of 72 h, which is the maximum time required for the biological assays. These results are in contrast to those obtained in our earlier work on other metal oxide NPs for which the hydrodynamic diameter and polydispersity typically increased in cell culture medium compared to water and continued to increase with storage time [ 22 , 23 ].…”
Section: Resultscontrasting
confidence: 99%
“…The agreement between measured SSA and manufacturer data was poor for more than half of the samples. It should be noted that the decrease in SSA for PVP and stearic-acid-modified NPs is consistent with our earlier results for both NiO and CeO 2 NPs [ 22 , 23 ]. In both cases, the measured SSA decreased slightly for the PVP-coated sample compared to the bare sample of the same size from the same supplier; there was a considerably larger decrease for samples containing stearic acid, which may indicate that the addition of a long chain fatty acid introduces issues with measurement of SSA.…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, the high surface reactivity of our NiO NPs (23.8 nM), as measured by ROS, would seem to suggest that the nanoparticles are quite reactive with possibly increased dissolution that would in turn result in a greater likelihood for toxicity. However, similar to the Kunc et al study, which reported that ROS did not appear to impact cytotoxicity [ 44 ], ROS did not appear to impact the acute toxicity results in our studies. Thus, as mentioned above, it appears that a factor that could be influential in determining acute toxicity is agglomeration/aggregation, which may have been responsible for the similar MMAD values of the MPs and NPs in the inhalation studies.…”
Section: Discussionsupporting
confidence: 89%
“…The BMC concentration was also expressed in terms of the SSA of each particle, which takes into account the available surface atoms for interaction, and which is proposed as a more appropriate dose metric for MONPs with negligible solubility compared to mass dose [ 64 ]. For the NPs used in this study, experimentally derived SSA values were available from recent publications [ 65 , 66 ]. However, for MPs, only the manufacturer-provided ranges were available (See Section 4 for details).…”
Section: Discussionmentioning
confidence: 99%